# Given a transformation of the plane F(x,y) = (2x+y,x-2y), find F^-1.

1. Apr 18, 2014

### kris89

1. The problem statement, all variables and given/known data
Given a transformation of the plane F(x,y) = (2x+y,x-2y), find F-1.

2. Relevant equations
Actually this exercise had an item (a) which I had to prove this is a transformation. So I proved this function is injective and surjective.

I know F(x,y) = (u,v) IFF F-1(u,v) = (x,y).

3. The attempt at a solution
I did it, but I don't know if this is the real solution...

F(x,y) = (u,v) IFF F-1(u,v) = (x,y).
u = 2x + y
v = x - 2y
Solving this, I concluded that: x = (v+2u)/5 and y = (u-2v)/5
Is this the solution? F-1 = ((v+2u)/5, (u-2v)/5) or do I have to do anything else?

2. Apr 18, 2014

### Staff: Mentor

Not quite. You should write the inverse as F-1(u, v) = ((v+2u)/5, (u-2v)/5).

You've done most of the work already. All that's left is to show that F-1(u, v) = (x, y). Replace u and v by what you have above, and use the formula for F-1 that you found.

Last edited: Apr 18, 2014
3. Apr 18, 2014

### HallsofIvy

Staff Emeritus
Alternatively, your teacher may prefer functions written in "x" and "y". In that case, replace your "u" with "x" and "v" with y: $F^{-1}(x, y)= ((y+ 2x)/5, (x- 2y)/5)$.